Supplementary cementitious materials in sandy soil improvement: a review - Al-Adhadh, Ahmed Raad; Daud, Nik Norsyahariati Nik; Yusuf, Badronnisa; Al-Rkaby, Alaa Hussein (Springer Science and Business Media LLC, 2024)
Sandy soil are mainly composed of sand-fine composite, and characterized by low shear strength in loose state, high permeability, high collapsibility potential when wetting, and high compressibility. Soil improvement is needed for these type of soils to modify the soil properties or fix some issues of the soil. There are different soil improvement techniques will be reviewed in this study. Chemical additives such as calcium based binders have some issues since they are considered a significant source of CO2 emissions and energy consumption. Another issue is that these materials change the behavior of treated soil from ductile to more brittle materials which lead to decrease the workability and the tensile strength of treated soil. The aim of this study is to focus on using supplementary cementitious materials SCMs as soil improvement agent as partially replacement of calcium based binders since these materials are more sustainable, reduce CO2 emissions by 50%, and economic and perform better or comparable results with that of the calcium based binders focusing on studies within the last ten years. The study meets the criteria: soil type (sandy soil), soil properties (UCS, compressibility, collapsibility, and permeability), and soil improvement techniques (chemical stabilizers, nano materials, green materials, and SCMs). The idea of using these materials is to reduce the pollution of using chemical stabilizers, improving the geotechnical properties of sandy soils, modifying the workability of soils treated with chemical additives, and increasing the tensile strength of soils. Reviewing the previous studies about various soils improvement techniques gives a clear vision of the importance and effect of these techniques to improve the performance of the sandy soils. Cement is more effective as a soil stabilizer compared to the other stabilizers due to its rapid hydration process. Considering the cost and effort of working, nano materials are more preferable due to their tiny particle size which facilitates easier storage and transportation. When used solely, SCMs have a humble effect on soil stabilization. For that, they are best used as a partial replacement for one of the chemical additives or in combination with an alkali activator.